ViewFinder: smartphone accessories for solo creators to self-monitoring during video recording for social media content - Mohd Nazar, Ahmad Azahari; Che Daud, Norhayati; Mohd Fadzludin, Isyraq Nur Hazriq; Abdullah, Mazlinda; Hasan, Zakiyah; P.Toyong, Natrina Mariane (Academica Press Solutions, 2023)
ViewFinder is a solution product as an additional accessory for a creator or solo designer of video content on social media. Nowadays, videos are easy to upload and download to social media sites that have become too many smartphone users to make it a new activity or career in the new media revolution now. The design of this additional accessory makes it easy for solo content creators to record themselves using the back of a smartphone camera, which we know is of better quality than using the front camera. This product uses a universal connection mount to connect to any existing tripod. Next, by placing the smartphone in the centre of the product, as the last step, the mirror is adjusted to get the correct direction of reflection from the screen to the user. With this product, users can easily use the back of the camera without worrying about the video while recording. Some features like slow-motion video and better quality not in the selfie camera (front) are solid reasons everyone should own this product. Almost everyone has a smartphone, so with this product, users do not have to invest their money to buy expensive cameras to create content that has good video quality.